2016
DOI: 10.1515/jomb-2016-0018
|View full text |Cite
|
Sign up to set email alerts
|

High Interleukin 27 Production is Associated with Early Clinical Stage and Localized Disease in Patients with Melanoma

Abstract: SummaryBackgroundThe immune response in patients with melanoma is an important focus of research due to the tumor’s resistance and immunotherapy possibilities. IL-27 is one of the cytokines with antitumor properties. The role of IL-27 in the pathogenesis of melanoma is still unclear. The aim of this study was to examine the association between serum IL-27 levels and the clinical parameters of melanoma patients.MethodsThe IL-27 concentration was determined by com mercial ELISA in serum samples from melanoma pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Similarly to our studies the serum level of IL-27 did not correspond with metastatic disease as it was shown in the example of melanoma. However, there is a lack of data about their role in exosomal cargo [47][48][49], but their high expression, in general, is one of the markers of response to immunotherapy. Although we did not detect the IL-6 in the UM patient-derived exosomes, we detected its soluble receptors, which may alter the sensitivity to IL-6 stimulation of cells exposed to these exosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to our studies the serum level of IL-27 did not correspond with metastatic disease as it was shown in the example of melanoma. However, there is a lack of data about their role in exosomal cargo [47][48][49], but their high expression, in general, is one of the markers of response to immunotherapy. Although we did not detect the IL-6 in the UM patient-derived exosomes, we detected its soluble receptors, which may alter the sensitivity to IL-6 stimulation of cells exposed to these exosomes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is also known as a potent inducer of the production of IL6 and IL8 in endothelial cells. It is highly expressed in the initial stages of CMM ( 89 ), stimulating the CMM growth and tumour vascularisation.…”
Section: The Microenvironment Of Cmm Participates In the Control Omentioning
confidence: 99%